Analysis Of Social Interaction Between Health Workers And Patients In Health Services - Achmad Hilal; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Abstract This study aims to analyze social interaction between healthcare workers and patients in healthcare Social services​ interaction plays a crucial role in determining service quality and patient satisfaction . This research uses a qualitative descriptive approach , with data collected through in- depth interviews , observations , and documentation . The results show that effective communication , empathy , and professional attitudes of healthcare workers significantly influence patient trust and comfort . Social interaction occurs in both verbal and nonverbal forms , where clear explanations and supportive body language enhance patient understanding . However , several barriers were identified , including limited consultation time , high workload , and differences in social and cultural backgrounds . Furthermore , the findings indicate a significant relationship between the quality of social interaction and patient satisfaction , as supported by a Chi- Square analysis . Good interaction improves patient compliance , reduces anxiety , and enhances overall healthcare outcomes . Therefore , improving interpersonal communication skills among healthcare workers is essential to achieve better healthcare service quality . Keywords : Social Interaction , Healthcare Workers , Patients , Communication , Patient Satisfaction